(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Security has always been a primary concern whether be it home or of fice. With the advent of information technology security over the infor mation acquired takes a prime concern. Security breaches are prevailing from technical to business field. Information technology has inundated the business sector and education world and every possible area one can think of. Consider the case of CERT-I n where, Hours ahead of its planned protest against certain incidents of internet censorship in India , hacker collective Anonymous attacked and brought down the website run by Computer Emergency Response Team India (CERT-I n). Amongst the most disastrous information leakage breach was the hacking of data for 1.5 million Master & VISA card users. VISA & MASTER card alerts banks about the security breach at Global Payments. The alert clearly stated that full Track 1 & Track 2 information was taken and could have been abused for counterfeit new cards. This information had been com promised from a period of January 21,2012 to February 25,2012. Yet it was not the company who disclosed the security breach, the security blogger Brian Krebs in security reported the event on 30,March,2012, This pattern is common for all security breaches as the conclusion who are impacted are the last ones to know about it. These threats to business need a stronger mechanism of security to counter them. Biometrics has offered new venues to resolve these issues.Biometrics refers to the physiological or behavioural characteristics of a person to authenticate his/her identity. This Biometrics is the most prominent and promising technique used for authenticating a person’s identity. Voice Biometrics, Finger printing, facial Recognition area few biometrics that are used for security purposes. This paper majorly cover Voice Biometrics. voice biometrics uses the pitch, tone, and rhythm of speech. Background noise, illness, age, and differences in telephones and microphones can cause problems with voice identification and au thorization.[Paper: exploration - voice -biometrics_1436] This is mostly used by Banks and Call Centres to authenticate there users. A telephone or microphone is required to proved your identity. Voice Biometrics is mostly adopted by the customers as they find it as a normal telephonic conversation. Remotely any customer from any location can login or use his/her ID. Each person has a unique voice and that can be easily stored in form of bits. So, this provide a better option for the developer or programmers to authenticate their software, databases etc using Voice Biometrics. Num ber of methods are used to apply these Biometrics. As a first step the new user has to record his/her speech by calling a telephone collection script. Once there is an existent recording the user is allowed to invoke an en rolment form and specify personal data, such as passwords and answers to questions on various topics, as suggested by the server. The answers can be selections from predetermined value lists, e.g. selected cities or colours, or user’s own new keywords. It is also possible to add new ques tions within the existent topics or dynamically generate these based on contexts or history of previous transactions or other events.